The Influence of Halal Awareness on Halal Food and Beverage Consumption among University Students - Khasanah, Ajeng; Huda, Nurul (Halal Science, 2025)
The increasing diversity of food and beverage products in modern markets raises concerns regarding Muslim consumers’ consistency in prioritizing halal-certified products. Although halal awareness has been widely discussed, empirical studies focusing on students within Islamic-based academic programs remain limited. This study aims to examine the relationship between halal awareness and halal consumption among undergraduate students of the Sharia Economic Law Program at UIN Raden Mas Said Surakarta. A quantitative approach was employed, involving 307 students from the 2019–2022 cohorts selected through proportional sampling. Data were collected using a structured questionnaire and analyzed using correlation and simple linear regression techniques. The results indicate a significant positive association between halal awareness and halal consumption (R = 0.690; R² = 0.476; t = 16.652; p < 0.001). Pearson’s correlation coefficient (r = 0.642) further demonstrates a moderately strong positive relationship between the two variables. These findings suggest that students with higher levels of halal awareness tend to exhibit stronger halal consumption behavior. However, the proportion of variance explained also indicates that factors beyond awareness may influence consumption decisions. The study highlights the importance of strengthening halal awareness through educational initiatives and institutional support as part of broader efforts to promote halal lifestyles. The results also provide insights for educational institutions and policymakers in developing strategies that support the sustainable growth of the halal industry, particularly among young consumers.